Evaluation of the influence of food intake on the incorporation and excretion kinetics of mesoporous silica particles in C.elegans. (25th January 2021) - Verdú, Samuel; Ruiz-Rico, María; Barat, José M.; Grau, Raúl
Abstract: The effect of the presence of food on the incorporation and excretion of silica particles was studied in this work using the biological model Caenorhabditis elegans and image analysis techniques. The experiment was based on two 24-hour phases: exposure and depuration. During exposure, nematodes were maintained for 24 h in liquid medium with silica particles, but some with and others without food. During depuration, nematodes were transferred to medium without particles. Nematodes were analysed by an image analysis in both phases to quantify the properties of particle distributions in nematodes' bodies with time. No differences were found in the proportion of nematodes carrying particles in the exposure phase when food was present. However in the depuration phase, lack of food generated a high proportion of particle carriers. Particle distribution properties were also similar in the exposure phase. Nevertheless, lack of food produced particle accumulation due to decelerated excretion because digestive tube relaxed under these conditions. Thus after the depuration phase, lack of food led particles to persist in digestive tubes. According to these results, intake of silica particles had no retention effects when a food flux was provided, but particles were not easily excreted when the food flux was interrupted. Graphical abstract: Image 1 Highlights: Presence of food on the digestion of particles was studied using C. elegans . The experiment was based on two 24-hour phases: exposure and depuration. Image analysis were used to study the particle distributions in nematodes' bodies. Lack of food generated a retention of particles inside nematodes. Distributions along digestive tubes generated different excretion velocities.